A promotion towards the usage of organic ingredient in soap / Muhammad Akmal Asyraaf Muhammad Azmi - Muhammad Azmi, Muhammad Akmal Asyraaf (Faculty of Art and Design, 2020)
Nowadays, Malaysia have too much skin care that contain prohibited substances that harm consumers health and it can cause cancer and death if not taken seriously.